2020
DOI: 10.7547/18-069
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Photodynamic Therapy in Infected Diabetic Foot Ulcers: A Multicenter Preliminary Experience

Abstract: Background: The increasing resistance of bacteria to antibiotics and the frequency of comorbid conditions of patients make the treatment of diabetic foot infections problematic. In this context, photodynamic therapy could be a useful tool to treat infected wounds. The aim of this study was to evaluate the effect of repeated applications of a phthalocyanine derivative (RLP068) on the bacterial load and on the healing process. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…The author had the same conclusion from the study as ours, namely that photodynamic therapy seems to represent a good alternative therapeutic choice for refractory chronic venous ulcers [ 21 ]. Monami et al performed A-PDT in patients with clinically infected ulcers who had been treated with RLP068 and demonstrated that the photosensitizer RLP068 under illumination seems to be a promising topical wound management procedure for the treatment of infected diabetic foot ulcers [ 22 ]. What process may underlie tissue healing after PDT?…”
Section: Discussionmentioning
confidence: 99%
“…The author had the same conclusion from the study as ours, namely that photodynamic therapy seems to represent a good alternative therapeutic choice for refractory chronic venous ulcers [ 21 ]. Monami et al performed A-PDT in patients with clinically infected ulcers who had been treated with RLP068 and demonstrated that the photosensitizer RLP068 under illumination seems to be a promising topical wound management procedure for the treatment of infected diabetic foot ulcers [ 22 ]. What process may underlie tissue healing after PDT?…”
Section: Discussionmentioning
confidence: 99%
“…Given the effectiveness and safety profile of the PDT-RLP068 system, along with preliminary data arising from clinical studies, 20 the addition of the PDT-RLP068 system to SoC was assumed to provide a benefit in terms of reduction of the time needed to reach a meaningful clinical target suggestive of the activation of the healing process (i.e., 40% reduction of the ulcers’ area). Accordingly, the effectiveness was measured in term of “additional days with clinical target achieved”.…”
Section: Methodsmentioning
confidence: 99%
“… 16 PDT could strongly contribute to wound healing of infected lesions through: immediate reduction of the local bacterial load; 17 effectiveness against all known classes of microorganisms; including wild type and resistant strains (also as biofilm status); 18 , 19 no induction of resistance as shown in vitro by multiple antimicrobial PDT treatments; 18 excellent safety and tolerability profile, thus safe for host tissues. 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore bacteria are not able to develop resistance even after multiple uses of PDT [ 18 ]. Recently, there have been many promising studies on the efficacy of phthalocyanines in photodynamic antimicrobial chemotherapy (PACT) [ 19 , 20 , 21 , 22 , 23 , 24 ]. In 2020, Monami et al published promising results of a clinical trial in which patients with diabetic foot ulcers underwent photodynamic therapy using a phthalocyanine derivative ( I , RLP068, Figure 1 ) as a PS [ 19 ].…”
Section: Introductionmentioning
confidence: 99%